4
$\begingroup$

Can I calculate the following limit without applying L'Hôpital?

$$\lim_{x\to\infty} x^2\operatorname{cos}\left(\frac{3x+2}{x^2}-1\right)$$

With L'Hôpital it gives me as a result $\frac{-9}{2}$.

$\endgroup$
  • 1
    $\begingroup$ How did you apply L'Hopital rule here? $\endgroup$ – Jack Oct 1 '17 at 14:19
  • $\begingroup$ You've mistyped the problem. $\endgroup$ – zhw. Oct 1 '17 at 16:52
0
$\begingroup$

I think he want to type and solve this $$\lim_{x\to\infty} x^2(cos(\frac{3x+2}{x^2})-1)=\frac{-9}{2}$$ this can be solve by multiplying conjugate $$\quad{\lim_{x\to\infty} x^2(cos(\frac{3x+2}{x^2})-1)=\\ \lim_{x\to\infty} x^2(cos(\frac{3x+2}{x^2})-1)\times \frac{cos(\frac{3x+2}{x^2})+1}{cos(\frac{3x+2}{x^2})+1}=\\ \lim_{x\to\infty} x^2(-\sin^2(\frac{3x+2}{x^2}))\times \frac{1}{cos(\frac{3x+2}{x^2})+1}=\\}$$ as $x\to \infty \implies \sin(\frac{3x+2}{x^2})\to 0 \implies \sin(\frac{3x+2}{x^2})\sim \frac{3x+2}{x^2}\\$so $$\quad{\lim_{x\to\infty} x^2(-\sin^2(\frac{3x+2}{x^2}))\times \frac{1}{cos(\frac{3x+2}{x^2})+1}=\\ \lim_{x\to\infty} -x^2(\frac{3x+2}{x^2})^2\times \frac{1}{cos(\frac{3x+2}{x^2})+1}=\\ \lim_{x\to\infty} -(\frac{(3x+2)^2}{x^2})\times \frac{1}{cos(\frac{3x+2}{x^2})+1}=\\\lim_{x\to\infty} -(\frac{9x^2+12x+4}{x^2})\times \frac{1}{cos(\frac{3x+2}{x^2})+1}=\\ \lim_{x\to\infty} -(\frac92)\times \frac{1}{cos(\frac{3x+2}{x^2})+1}=\\ -(\frac92)\times \frac{1}{cos(0)+1}=\\\frac{-9}{2}}$$

$\endgroup$
  • $\begingroup$ @trick15f :please look at my answer !>? $\endgroup$ – Khosrotash Oct 1 '17 at 15:37
  • $\begingroup$ @MariosGretsas : I saw the question , I saw the answer $\frac{-9}{2}$ and then think ,may be this $\endgroup$ – Khosrotash Oct 1 '17 at 16:28
  • 1
    $\begingroup$ @Khosrotash thank you very much, I understood everything $\endgroup$ – trick15f Oct 1 '17 at 16:28
  • $\begingroup$ @trick15f : please explain How you do a mistake in writing question ! $\endgroup$ – Khosrotash Oct 1 '17 at 16:29
0
$\begingroup$

Since $$\lim_{x\to\infty} \operatorname{cos}\left(\frac{3x+2}{x^2}-1\right)=\cos1>0,$$ we obtain

$$\lim_{x\to\infty} x^2\operatorname{cos}\left(\frac{3x+2}{x^2}-1\right)=+\infty$$

Maybe do you mean $$\lim_{x\to\infty} x^2\operatorname{cos}\left(\frac{3x+2}{x^2}-\frac{\pi}{2}\right)=\infty?$$

$\endgroup$
  • $\begingroup$ You used that $f(x)=\cos x$ is an even and continuous function. $$\lim_{x\to \infty}\left(\frac{3x+2}{x^2}-1\right)=$$ $$=\lim_{x\to \infty}\left(\frac{\frac{3}{x}+\frac{2}{x^2}}{1}-1\right)=$$ $$=\frac{0+0}{1}-1=0-1=-1$$ and $\cos (-1)=\cos 1$. $\endgroup$ – user236182 Oct 1 '17 at 14:36
  • $\begingroup$ @user236182 Yes of course! $\endgroup$ – Michael Rozenberg Oct 1 '17 at 14:42
0
$\begingroup$

We have to find the limit of :

$$\lim\limits_{x \to \infty}x^2(cos(\frac{ax+b}{x^2})-1)=?$$

If we put the substitution $x=\frac{1}{y}$ and use the formula $1-2sin(x)^2=cos(2x)$ we get : $$\lim\limits_{y \to 0}\frac{-2sin(\frac{(ay+by^2)}{2})^2}{y^2}$$ Wich equivalent to : $$\lim\limits_{y \to 0}\frac{(ay+by^2)^2}{4}\frac{-2sin(\frac{(ay+by^2)}{2})^2}{y^2\frac{(ay+by^2)^2}{4}}$$ Or $$\lim\limits_{y \to 0}\frac{-sin(\frac{(ay+by^2)}{2})^2}{\frac{(ay+by^2)^2}{4}}=-1$$ Because : $\lim\limits_{z \to 0}\frac{sin(z)}{z}=1$

So we have :

$$\lim\limits_{y \to 0}\frac{(ay+by^2)^2}{4}\frac{-2sin(\frac{(ay+by^2)}{2})^2}{y^2\frac{(ay+by^2)^2}{4}}=\lim\limits_{y \to 0}\frac{(ay+by^2)^2}{4}\frac{-2}{y^2}=\frac{-a^2}{2}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.